Exploration of [2 + 2 + 2] cyclotrimerisation methodology to prepare tetrahydroisoquinoline-based compounds with potential aldo–keto reductase 1C3 target affinity. Issue 8 (9th July 2019) - Santos, Ana R. N.; Sheldrake, Helen M.; Ibrahim, Ali I. M.; Danta, Chhanda Charan; Bonanni, Davide; Daga, Martina; Oliaro-Bosso, Simonetta; Boschi, Donatella; Lolli, Marco L.; Pors, Klaus
Abstract : Tetrahydroisoquinoline (THIQ) is a key structural component in many biologically active molecules including natural products and synthetic pharmaceuticals. Abstract : Tetrahydroisoquinoline (THIQ) is a key structural component in many biologically active molecules including natural products and synthetic pharmaceuticals. Here, we report on the use of transition-metal mediated [2 + 2 + 2] cyclotrimerisation of alkynes to generate tricyclic THIQs with potential to selectively inhibit AKR1C3.